Internet of things, smart spaces, and next generation networks and systems : 14th International Conference, NEW2AN 2014 and 7th Conference, ruSMART 2014, St. Petersburg, Russia, August 27-29, 2014. Proceedings - Andreev, Sergey; Koucheryavy, Yevgeni; Balandin, Sergey (Lecture Notes in Computer Science, 2014)
This book constitutes the joint refereed proceedings of the 14th International Conference on Next Generation Wired/Wireless Advanced Networks and Systems, NEW2AN 2014, and the 7th Conference on Internet of Things and Smart Spaces, ruSMART 2014, held in St. Petersburg, Russia, in August 2014. The total of 67 papers was carefully reviewed and selected for inclusion in this book. The 15 papers selected from ruSMART are organized in topical sections named: smart spaces core technologies, smart spaces for geo-location and e-tourism apps, smart space supporting technologies, and video solutions for smart spaces. The 52 papers from NEW2AN deal with the following topics: advances in wireless networking, ad hoc networks and enhanced services, sensor- and machine-type communication, networking architectures and their modeling, traffic analysis and prediction, analytical methods for performance evaluation, materials for future communications, generation and analysis of signals, business aspects of networking, progress on upper layers and implementations, modeling methods and tools, techniques, algorithms, and control problems, photonics and optics, and signals and their processing.